Gratitude: Basic Character in Islamic Education - Afandi, Nur Kholik; Wiguna, Alivermana; Tajab, Muh.; Setiawan, Wahyudi (ISTAWA, 2022)
Gratitude is teaching about morality that concerns all aspects of human life. This study aims to determine the spiritual values of gratitude in the Qur'an in relation to character in Islamic education. Through a subjective-cum-objective hermeneutic approach, the research results show that gratitude contains several character values that are needed in Islamic education. These character values include, amanah, qonÄ'ah, istiqÄmah, tawÄá¸u', tawakal, optimistic, creative, hard work and social care. The results of this study indicate that gratitude is the main character that contains religious and social character values based on belief and faith in God. These character values are needed in achieving the goals of Islamic education.